Pengujian Kekuatan Rangka Sepeda Tipe Diamond Frame Material AISI 4130 dan Metode Finite Element - Mulki Firdaus, Muhammad (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
The bicycle frame is crucial as it serves as the primary structure that sustains all other components of a bicycle. The bicycle frame must possess the capacity to endure the weight of the rider and effectively dampen the impact of road shocks. Hence, meticulous design is important while constructing a bicycle frame. In order to facilitate the examination of frame strength, it is imperative to conduct frame strength analysis through the utilization of Autodesk Inventor 2023. The material utilized is AISI 4130. The findings of the static simulation indicate that the maximum Von Mises stress value is 48 MPa. The maximum displacement is 0.12 millimetres. The minimum safety factor is 5.7 ul. The study simulation of more than 1.5 ul indicates that the frame design meets good safety criteria, since the Von Mises stress value is ≤ 400 MPa.